TORSION OF TESTIS – REPORT OF TWO CASES WITH A BRIEF REVIEW OF LITERATURE - Thamilselvam P; Karmegan M; Pandurangan T (Asian Journal of Medicine & Health Sciences, 2020)
The torsion of testis is an acute vascular event, one of the emergency presentations seen in young adolescent males. The spermatic cord becomes twisted and rotated on its axis and results in gangrene of testis due to vascular ischemia. There may be chances of loss of normal spermatogenetic function if there is any delay in the management of testicular torsion. We had 2 cases of torsion testis with classical signs and symptoms with acute pain over the scrotum, elevated testis & swelling on affected side. Emergency ultrasound and Doppler were done and reported as torsion testis with ischemia. The cases were managed with orchiectomy since the patients reported to us late. Patients were comfortable in post-operative period and discharged. In conclusion, testicular torsion should be considered in undescended testis. The emergency Ultrasound and Doppler investigations have to be done in all cases of acute scrotum who have acute pain over scrotum.